Risk Perception among Commercial Drivers and Compliance with Third Party Motor Insurance Policy - Gbenga, Alli Noah (International Journal of Social Science and Business, 2025)
Third-party motor insurance is a great challenge among the commercial drivers of the Lagos State in Nigeria, even though the insurances are mandatory and have an emphasis on road safety. The study adopted cross-sectional survey research design whereby it was used to collect information about a sample of 362 commercial drivers in Lagos State. Descriptive analysis and regression were used in order to test the relationships between the independent variables and that of compliance behavior. The results validate the fact that the perception of risk is a complex concept that has a great and direct influence on compliance with third-party motor insurance. The four factors of driving experience and exposure, cultural beliefs together with social norms, economic benefits that were expected, and trust towards insurance providers, were found to have significant positive effects in the regression. Conspicuously, the mistrust towards insurers and the feeling that premiums are a financial burden are significant barriers and, in most cases, supercharged by fatalistic cultural ideologies. The findings reinforce the concept that compliance resides not only in legal concerns but exists due to a multidimensional contention of mental, societal, and economic dispositions.